2019
DOI: 10.1002/jaba.592
|View full text |Cite
|
Sign up to set email alerts
|

Producing mands in concurrent operant environments

Abstract: This study examined strategies designed to increase the rate of targeted, low-probability mands in a concurrent operant environment. We examined the effects of schedule manipulations, prompt manipulations, motivating operation manipulations, and combined behavioral process manipulations. Increases in target mands were produced for all 8 participants. Schedule manipulations were effective in producing increased rates of targeted mands for 3 of 8 participants, whereas prompt manipulations were effective for 4 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 39 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…An effective procedure to increase target manding in a concurrent operant environment was found for all three participants. Saif and Hamdan's results replicate those of Seaver and Bourret (2020) by demonstrating the effectiveness of the concurrent FR 1 RI 30-s schedule plus prompting. These data add further support for use of this intervention when the concurrent FR 1 RI 30-s schedule alone does not produce increases in target manding.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…An effective procedure to increase target manding in a concurrent operant environment was found for all three participants. Saif and Hamdan's results replicate those of Seaver and Bourret (2020) by demonstrating the effectiveness of the concurrent FR 1 RI 30-s schedule plus prompting. These data add further support for use of this intervention when the concurrent FR 1 RI 30-s schedule alone does not produce increases in target manding.…”
Section: Discussionmentioning
confidence: 63%
“…In their review paper on promoting behavior variability, Wolfe et al (2014) found lag schedules of reinforcement, reinforcement of novel responding, concurrent schedules of reinforcement, and prompting were all effective treatments for promoting varied responding. Several researchers have looked specifically at manipulating concurrent schedules of reinforcement to produce varied manding for previously established mands (Bernstein & Sturmey, 2008;Seaver & Bourret, 2020). Bernstein and Sturmey (2008) modified the distribution of manding for previously established mands for two participants with ASD.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it could be beneficial to ensure that generic interactions such as praise and conversation are reinforcing before delivering them as consequences for any given client, rather than assuming they are reinforcers and including them for all clients. In contrast, if the assessment indicates social interaction is neutral or aversive for a given individual, then interventions can be implemented to condition social interactions as reinforcers (e.g., Axe & Laprime, 2017; Dozier et al, 2012), facilitate acquisition of fundamental social or play skills (e.g., joint attention, Taylor & Hoch, 2008; mands, Seaver & Bourret, 2020), and reduce or prevent social avoidance and corresponding problems. Moreover, the results of assessments of sociability may provide a more naturalistic, general dependent measure with which to evaluate the effects of these interventions.…”
mentioning
confidence: 99%